EMPOWERMENT IN SOCIAL WORK - Gvaldaitė, Lijana (Socialinė teorija, empirija, politika ir praktika, 2009)
The article analyses the process of empowerment which is applied in social and community psychology as well as in practical social work, particularly on the level of community models. There is a shortage of comprehensive studies and researches about empowerment in Lithuania. The article presents the theoretical concept of empowerment and, based on analysis of practical cases and interview, reveals its practical manifestation in individual and community support models. Research methods: comparative analysis of scientific literature, case study, interview with leaders of family self-help groups (experts) and participants of Lithuania and Lombard region, Italy.
Keywords: Social work; Empowerment; Self-help groups; Community work